Migrasi Penduduk dari Kampung Bebanir ke Kampung Sei Bebanir Bangun Kabupaten Berau Tahun 1980–1985 - Indah Rahmawati; Sainal A; Norhidayat Norhidayat; Muhamad Sopyan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study discusses the migration of residents from Bebanir Village to Sei Bebanir Bangun Village in Berau Regency during 1980–1985, which was prompted by environmental and health conditions that did not support community life. The study aims to analyze the factors influencing migration, the process of population relocation, and the adaptation patterns of the community after settling in a new environment. The research uses historical methods with a qualitative approach through the stages of heuristics, source criticism, interpretation, and historiography. Data collection techniques were carried out through interviews, observation, and documentation studies. The results of the study indicate that migration was influenced by seawater intrusion causing a clean water crisis, limited health facilities, regional isolation, as well as relocation support from the government. The migration process took place gradually and collectively through river routes until the community settled in Sei Bebanir Bangun Village. In the process of adaptation, the community was able to build a new life by developing the agricultural and fisheries sectors, strengthening social relationships based on mutual cooperation, and preserving local cultural values. This study concludes that migration is not only a form of population movement but also a social change process that impacts the improvement of community quality of life and the formation of more livable settlements.